Underestimated virus impaired cognition-more evidence and more work to do - Awan, Maher Un Nisa; Mahmood, Faisal; Peng, Xiao-bin; Zheng, Fenshuang; Xu, Jun (Frontiers in Immunology, 2025)
Neurodegenerative disorders (NDs) are chronic neurological diseases that can be of idiopathic, genetic, or potentially infectious origin. Although the exact cause of neurodegeneration is unknown, it might be result of a confluence of age, genetic susceptibility factors, and environmental stresses. The blood-brain barrier shields the brain from the majority of viral infections, however neurotropic viruses are able to breach this barrier and infect central nervous system. Growing research points to a possible connection between viruses and neurodegenerative diseases, indicating that virus-induced neuroinflammation and disruption of neuronal protein quality control may play a role in the initial stages of disease progression. The diagnosis and treatment of NDs are urgent and challenging. Even though there is limited clinical evidence to support the use of antiviral medications and their dose regimens within the central nervous system (CNS), with the exception of acyclovir, they are currently utilized to treat various viral CNS infections. Understanding the neuropathogenesis of viral CNS infection may help with targeted diagnosis and treatment plans by focusing on the molecular mechanisms of the CNS. It may also be helpful in the search for new antiviral drugs, which are crucial for better managing these neurotropic viral infections. This review focuses on new findings linking viral infection to NDs and explores how viral modifications of cellular functions can impact the development of neurodegeneration and will also explore the therapeutic potential of antiviral drugs in NDs.